2006
DOI: 10.1007/s10653-005-9032-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural organic matter on arsenic release from soils and sediments into groundwater

Abstract: Arsenic (As) contamination in groundwater has received significant attention recently. Natural and anthropogenic sources contribute to the worldwide occurrence of As contamination. As speciation is an important factor related to its toxic and mobile behavior. The release of As from soils and sediments into groundwater is governed by several geophysicochemical processes, of which, As sorption behavior is of principle significance. This review paper summarizes existing information regarding the effects of natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
187
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 402 publications
(210 citation statements)
references
References 112 publications
5
187
0
7
Order By: Relevance
“…pH and P were important direct factors governing the mobility of As in soil. It has been reported that sequestration of As from of Fe-Mn oxides of mineral surfaces was consistently increasing with lower pH (Signes-Pastor et al 2007;Wang and Mulligan 2006;Yang et al 2002), because low pH values could lead to the formation of more positively charged Fe oxides, and then positively charged Fe oxides could adsorb more As anions on the mineral surface (Lafferty and Loeppert 2005;Jain et al 1999). In this research, NPK + M and M treatments have led to a slight increase of pH, but other treatments were opposite.…”
Section: Factors Governing the Difference Of Bioavailable Asmentioning
confidence: 51%
See 3 more Smart Citations
“…pH and P were important direct factors governing the mobility of As in soil. It has been reported that sequestration of As from of Fe-Mn oxides of mineral surfaces was consistently increasing with lower pH (Signes-Pastor et al 2007;Wang and Mulligan 2006;Yang et al 2002), because low pH values could lead to the formation of more positively charged Fe oxides, and then positively charged Fe oxides could adsorb more As anions on the mineral surface (Lafferty and Loeppert 2005;Jain et al 1999). In this research, NPK + M and M treatments have led to a slight increase of pH, but other treatments were opposite.…”
Section: Factors Governing the Difference Of Bioavailable Asmentioning
confidence: 51%
“…7 Comparison of BCR-SEPs-determined As (F1, F2) with the biosensor-determined As at the three As addition levels: 0 mg/kg, 50 mg/kg, and 100 mg/kg Jackson et al 2006;Mladenov et al 2010). Although there is no direct conclusion to prove that As bound with organic carbon is available by biosensor cell, however, interactions between organic carbon and As can be influenced by various factors such as pH, redox potential, and other competing ions in aquatic environments, and it could cause the secondary release of As to aquatic environments and the rise of bioavailable As (Wang and Mulligan 2006). pH and P were important direct factors governing the mobility of As in soil.…”
Section: Factors Governing the Difference Of Bioavailable Asmentioning
confidence: 99%
See 2 more Smart Citations
“…Several mechanisms might be responsible for the decreased Se mobility under acidic conditions in SOM-rich samples. Firstly, there is less mineral dissolution occurring due to the stabilization by SOM (Wang and Mulligan, 2006) as confirmed by lower Al and Fe leachate concentrations (Table A1). Secondly, new adsorption sites can be formed on humic acid or metal-humus complexes (Kamei-Ishikawa et al, 2007).…”
Section: Role Of Organic Mattermentioning
confidence: 96%